Current Treatment Options for Penile Fractures - Jack, Gregory S (MedReviews, LLC, 2004)
The diagnosis of “penile fracture” describes the traumatic rupture of the tunica albuginea of an erect penis. Penile fractures typically occur when the engorged penile corpora are forced to buckle and literally “pop” under the pressure of a blunt sexual trauma. Patients typically describe immediate detumescence, severe pain, and swelling as a result of the injury. Prompt surgical exploration and corporal repair is the most efficacious therapy. Although a majority of cases can be diagnosed from the history and physical examination alone, radiographic studies, including retrograde urethrography and corporal cavernosography can aid in the diagnosis of unusual cases.